A Study of Certain Phases of Undergraduate Teacher Education in NCATE Accredited Institutions - Burgess, Phyllis; Wichita State Univ., KS. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This study focuses on significant changes in undergraduate teacher education. In June 1971, a questionnaire was sent to institutions accredited for undergraduate teacher education. The data of this report is based on replies from 238 institutions located in 47 states. Of the responding institutions, 29 percent are located in metropolitan areas with a population over 300,000, and 68 percent report their undergraduate students are required to take one introductory course in professional education. Responses to the questionnaire indicate a desire for significant changes in the improvement and expansion of field experience in undergraduate teacher education. The figures, however, indicate four areas of consideration before the aims can be implemented: 1) There is a relatively low percentage of institutions engaging in preparing students for inner-city schools; 2) There is a definite lack of communications contributing to the disorganization of teacher education programs; 3) There is no common agreement of appropriate content for required introductory course; and 4) There is a number of institutions reporting no changes in their teacher education programs over the last 5 years. (MJM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Programs; Teacher Education; Teacher Education Curriculum; Teaching Experience